Impact of Vitamin D on Skin Aging, and Age-Related Dermatological Conditions - Sankalya S. Ambagaspitiya; Gayan A. Appuhamillage; Sunil J. Wimalawansa (Frontiers in Bioscience-Landmark)
Human skin is a physical and biochemical barrier that protects the internal body from the external environment. Throughout a person’s life, the skin undergoes both intrinsic and extrinsic aging, leading to microscopic and macroscopic changes in its morphology. In addition, the repair processes slow with aging, making the older population more susceptible to skin diseases. Intrinsic factors associated with advanced age gradually degrade the dermal collagen matrix, resulting in fine wrinkles and reduced elasticity; this is accelerated in post-menopausal women due to estrogen deficiency. In contrast, extrinsic factors associated with advanced age, primarily caused by exposure to ultraviolet (UV) radiation, lead to coarse wrinkles, solar elastosis, hyperkeratosis, irregular pigmentation, and skin cancers. UVB radiation, while contributing to skin photo-aging, also induces the cutaneous synthesis of vitamin D. Vitamin D, in turn, protects the skin from oxidative stress, inflammation, and DNA damage, thereby delaying both chronological and photo-aging. Moreover, research has demonstrated an association between lower vitamin D levels and a higher prevalence of certain cutaneous diseases. This review explores and summarizes the critical role of vitamin D in skin aging and age-related skin diseases. The data presented highlight the importance of maintaining vitamin D adequacy throughout life.